2005
DOI: 10.1007/s11230-005-5496-5
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating morphometric protocols using polystome marginal hooklet measurements

Abstract: The flexible body structure of polystomes (Monogenea: Polystomatidae) encumbers taxonomic classification and species identification. Large intraspecific and limited interspecific variation in the morphology of polystomes further complicates the identification of species. Apart from employing the host-specific nature of the polystomes, taxonomic characterisation relies heavily on the sclerotised skeletal structures, such as the hamuli and the marginal hooklets. The currently accepted measurement system for marg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Measurements were taken using Eclipse network software (Nikon). Marginal hooklet measurements were obtained from the oncomiracidia that hatched from incubated eggs, following the protocol developed by Du Preez and Maritz (2006).…”
Section: Methodsmentioning
confidence: 99%
“…Measurements were taken using Eclipse network software (Nikon). Marginal hooklet measurements were obtained from the oncomiracidia that hatched from incubated eggs, following the protocol developed by Du Preez and Maritz (2006).…”
Section: Methodsmentioning
confidence: 99%
“…As already emphasised by several authors, most morphological features of the haptoral hard parts are indeed highly correlated (e.g. Shinn et al, 1996;Du Preez & Maritz, 2006), and traditional discriminant methods cannot properly accommodate such multicollinearity. This is especially true for small sample sizes where several morphological measurements are used to classify a few individuals [for a comprehensive report and ways to handle multicollinearity, see Vignon (2011)].…”
Section: Trusses and Diagnosesmentioning
confidence: 98%
“…I voluntarily discarded the few publications dealing with morphometrics using a wide range of methods and measurement (e.g. Shinn et al, 1996;Du Preez & Maritz, 2006). While several methods of shape retrocalculation based on linear measurements exist, figures were drawn by hand with the help of a custom-made transparent rule previously calibrated on a computer with Adobe Illustrator.…”
Section: Bibliographic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Gussev (1976) has indicated a complex system of measurements to correctly identify monogenean species. However, several studies demonstrated that many morphometric variables are highly intercorrelated, which diminishes their value to discriminate species (Shinn et al 1996;Du Preez and Maritz 2006;Vignon 2011a,b). This problem is particularly important in closely related species (Strona et al 2005).…”
Section: Introductionmentioning
confidence: 99%